THE INFLUENCE OF THE ACTIVITIES OF THE ISLAMIC SPIRITUAL ORGANIZATION (ROHIS) ON SOCIAL BEHAVIOR IN THE SCHOOL ENVIRONMENT OF STUDENTS AT THE 17 STATE HIGH SCHOOL MAKASSAR (International Conference on Social and Islamic Studies, 2022)
This study aims to: (1) describe the activities of the ROHIS organization at 17 State HighA Negeri 17 Makassar. (2) describe the social behavior of students at 17 State High School Makassar, and (3) analyze the influence of students' activities in ROHIS organizational activities on the social behavior of students in the school environment at 17 State High School of Makassar. This research is a population research, namely research whose purpose is to collect information about variables from a group of objects (population). While the type of research is quantitative, namely research conducted by collecting data in the form of numbers which are then processed and analyzed to obtain information. This research was conducted at 17 State High School Makassar which is located at Sunu road, Makassar City with a population of 88 students where this population is also the object of research because the total population is less than 100 people. The instrument used in this study was a list of statements to find out how influential the ROHIS organization's activities were. All data were analyzed using descriptive statistical analysis using product moment correlation analysis techniques which were then analyzed using simple regression analysis to test the hypotheses that had been proposed. This study shows that: (1) the activity level of students in the ROHIS organization at 17 State High School Makassar is included in the good category, which is in the interval 33-42 with a percentage of 68.18%. (2) the social behavior of 17 State High School Makassar students is included in the good category at the interval of 62-80 with a percentage of 63.64%. (3) There is an influence of the ROHIS organizational activity variable (X) on the social behavior of students (Y). Evidenced by the results of the simple linear regression equation where the regression coefficient has a value of 0.260 where every 1% increase in ROHIS organizational activities (X) then social behavior (Y) will increase. And also the regression coefficient which is positive indicates that ROHIS organizational activities (X) have a positive effect on social behavior of students (Y) with the regression equation Y = 60, 621 + 0.260X. The results of the hypothesis test also show a significance value (Sig.) of 0.003 which is smaller than the probability value of 0.05 so that it can be said that "There is an Influence of ROHIS Organizational Activities on Students' Social Behavior" The implications of this research are: 1) If teachers and schools can better support the activities of students in the Spiritual Islamic organization (ROHIS), then students will be more enthusiastic about participating in activities carried out by the Spiritual Islamic organization (ROHIS) and will also more formed good behavior for students. 2) this activity is very beneficial for students, so positive activities such as ROHIS organizational activities can be carried out continuously. 3) This research was constrained by the conditions of the Covid 19 pandemic, which prevented researchers from interacting directly with students. For other researchers who wish to research in the same study area, it is hoped that they can further develop activities that can shape student behavior.